Positive effects of augmented feedback to reduce time on ground in well-trained runners - Gilgen-Ammann, R.; Wyss, T.; Troesch, S.; Heyer, L.; Taube, W. (International Journal of Sports Physiology and Performance, 2018)
Context: Successful elite sprint to long-distance runners are known to have shorter ground-contact time (GCT) than their less successful counterparts. Purpose: To investigate whether augmented feedback (aF) about GCT can reduce the time on ground (TOG) per minute in long-distance runners and, if so, whether this reduction improves running performance. Methods: Thirty well-trained runners were allocated to 3 groups. The intervention group (IG) received visual aF about their GCT during 8 high-intensity interval sessions in the 4-wk training period and were instructed to minimize GCT. The 1st control group (CG1) trained with the IG but was not given any feedback. The 2nd control group (CG2) followed their own training routine. Data were obtained pre- and postintervention for all 3 groups. The dependent variable was TOG per minute, computed from step frequency and GCT. Results: The IG significantly reduced TOG (P=.043, -1.7%, 90%CL -3.1;-0.3) and improved their mean 10×400-m performance time (P<.001, -1.5%, 90%CL -1.9;-1.1). In contrast, the 2 control groups revealed unchanged values, indicating that normal high-intensity training and an individualized routine without aF were not able to reduce TOG. The fact that CG1 received the same instructions and participated in the same training sessions as the IG underlined that aF was crucial to reduce TOG. Conclusions: The provision of aF about GCT seems to be a promising approach that should be considered during training practice of well-trained runners.